Differences of Misoprostol and Oxytocin Effect on Cervical Ripening - Yunitra, Imelda; Lasmini, Putri Sri; Bachtiar, Hafni (Andalas Obstetrics And Gynecology Journal, 2019)
Many studies has been done to determine the effectiveness of misoprostol and oxytocin even comparing the use of them for the induction of labor. Based on those studies, there seems to be a different effect of misoprostol and oxytocin on different phase of parturition, start from cervical ripening, uterine contrac- tion and successful labor. Compared to oxytocin as cervical ripening agent, misoprostol is more avail- able, cheaper, and effective. This study was an experimental study using pre-post control group to eval- uate the difference of misoprostol and oxytocin effect on cervical ripening. This study was conducted at RSUP DR. M. Djamil Padang and Secondary Hospital in periode of January-October 2014. Indepen- dent variable was cervical ripening using misoprostol 25 µg and oxytocin drip. Dependent variables are the event of cervical ripening and the increase of Bishop score. The average of cervical ripening using misoprostol was higher than oxytocin with 7,0968 ± 2,11904, compared to 2,5806±3,36427. This difference was significantly different with p > 0.05. It can be concluded that misoprostol is a better cer- vical ripening agent than oxytocin. Oxytocin is better given to ripe cervixKeywords: severe preeclampsia, folic acid, normal pregnancy